Statistical services in ten years' time : the operational environment, organization and coordination, an ideal system, use of computers, setting priorities, technical developments : report of a seminar of the Conference of European Statisticians, a joint body of the United Nations Economic Commission for Europe, Washington D.C., 21-25 March 1977 - Duncan, Joseph W.; Brady, Bennett M.; United Nations (Oxford ; New York : Published for the United Nations by Pergamon Press, 1978)
This book shows the impact of technical development on statistical policy in 1980s
Includes bibliographical references.
mf 22/01/2019
Loans
Keywords: Statistical services; Statistics